Investigation of MQL and CNC turning parameters on the machinability of unreinforced polypropylene: study of surface roughness, temperature, and specific cutting energy - Hamdi, Amine; Yapan, Yusuf Furkan; Uysal, Alper; Merghache, Sidi Mohammed (SPRINGER LONDON LTD, 2024)
The main aim of this study was to evaluate the ease of machining unreinforced polypropylene (PP), focusing on surface quality (Ra), cutting temperature (T), and specific cutting energy (E-cs) during turning. We conducted experimental tests using both dry machining and minimum quantity lubrication (MQL) conditions. We analyzed key factors such as cutting speed (V-c), feed (f), depth of cut (ap), and nose radius (r(epsilon)) using Pareto analysis, response surface methodology (RSM), and the desirability function (DF) to study and optimize both dependent and independent parameters. It is important to note that the influence of MQL on the machinability of polymers has not been extensively explored in existing scientific literature. Therefore, this study provides valuable insights for the sustainable development of MQL machining for polymer materials. Our findings indicate that using MQL and reducing the feed (f) improved the machinability of PP, resulting in better surface quality, lower cutting temperatures, and reduced specific cutting energy (SCE) consumption. Using the DF method, we identified the optimal combination of independent parameters, which includes a high cutting speed (V-c = 500m/min), a low feed (f = 0.12mm/rev), a deep cut (ap = 2.6mm), and a small nose radius (r(epsilon) = 0.4mm).
Keywords: Polypropylene PP; Turning; Pareto chart; RSM; Desirability function; MULTIOBJECTIVE OPTIMIZATION; TOOL WEAR; AISI 420; CONSUMPTION; PREDICTION; FORCE; TITANIUM; ANN; PERFORMANCE; Automation & Control Systems; Engineering